2013
DOI: 10.1002/cad.20036
|View full text |Cite
|
Sign up to set email alerts
|

When Is Sport Participation Risky or Protective for Alcohol Use? The Role of Teammates, Friendships, and Popularity

Abstract: Little is known about how adolescents' peer relations might alter whether sport participation is associated with alcohol use. Consistent with social learning theory, we found that sport participation was protective against alcohol use if these peers had low alcohol use, but athletes were likely to use alcohol if their sport friends and teammates had high alcohol use. Interestingly, those with no or low sport participation seemed to emulate the alcohol use of their non-sport friends, whereas adolescents in a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…It has been suggested that sport participation may prevent problem behavior during adolescence, and this contention also concurs with etiological theories [ 26 , 27 ]. However, studies more often did not than did confirm protective effects of participation in sport against alcohol consumption in youth [ 25 , 28 , 29 , 30 ]. In brief, since some investigators reported sports as being protective against drinking alcohol [ 31 ], a great deal of studies highlighted sports participation as a factor contributing to increased risk for alcohol consumption and binge drinking [ 25 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that sport participation may prevent problem behavior during adolescence, and this contention also concurs with etiological theories [ 26 , 27 ]. However, studies more often did not than did confirm protective effects of participation in sport against alcohol consumption in youth [ 25 , 28 , 29 , 30 ]. In brief, since some investigators reported sports as being protective against drinking alcohol [ 31 ], a great deal of studies highlighted sports participation as a factor contributing to increased risk for alcohol consumption and binge drinking [ 25 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies more often did not than did confirm protective effects of participation in sport against alcohol consumption in youth [ 25 , 28 , 29 , 30 ]. In brief, since some investigators reported sports as being protective against drinking alcohol [ 31 ], a great deal of studies highlighted sports participation as a factor contributing to increased risk for alcohol consumption and binge drinking [ 25 , 28 , 29 , 30 ]. Again, differences in observed associations are explained regarding differences in the type of sport (i.e., differential influence of individual- and team-sport participation) [ 25 ], sex-specific factors [ 32 ], the level of sport participation (i.e., sport achievement) [ 23 ], social circumstances (i.e., parental influence, socioeconomic status) [ 25 ], and the role of teammates, friendship and popularity [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peer relations and factors related to family structure and parent-child relationships have received particular attention in this respect. Research consistently shows that peer drinking increases adolescents' alcohol use (Cruz et al, 2012;Fujimoto and Valente, 2012;Overbeek et al, 2010;Vest and Simpkins, 2013). Research also indicates that family-related variables, such as parental monitoring, time spent with parents and family structure, influence adolescent drinking (Barnes and Farrell, 1992;Dishion and McMahon, 1998;Flannery et al, 1999;Thorlindsson et al, 2007;Warr, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, engagement in sports and alcohol use exhibited a significant interaction with gender, with elevated risks for boys but not girls. Vest and Simpkins (2013) found that athletes were likely to use alcohol if their sports friends and teammates had high alcohol use, suggesting that the association between engagement in sports and alcohol use is mediated through peer relations. Mays et al (2010) found that after controlling for demographics and sports-specific factors, perceived peer drinking was significantly associated with total alcohol-related behaviors among U.S. high school adolescents.…”
Section: Discussionmentioning
confidence: 98%